PENGELOLAAN DANA DESA DALAM PENINGKATAN PEMBANGUNAN DESA LEPPANGENG KECAMATAN AJANGALE KABUPATEN BONE - haeranah haeranah (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2020)
This study aims to describe and analyze the management of village funds in increasing development in the village of Leppangeng, the obstacles that occur in its application, and the efforts that can be made in overcoming various obstacles. This study uses a qualitative descriptive method by collecting data through interviews and observations and documentation. The results showed that the implementation of the Village Fund in Leppangeng Village had been carried out well and effectively in the field of development, but it was still efficient in its use. However, the realization of the use of village funds in 2018 has decreased compared to previous years due to various obstacles. The commitment of the central government, regional government, and village government to jointly succeed in the success of the village fund policy, especially in terms of increasing the competence of the apparatus in the village in terms of knowledge of the application of the village financial system.